Conventional and molecular characterization of Vibro parahaemolyticus, vibrio alginolyticus and vibro vulnificus in oyster, crassostrea iredalei from east coast , Malaysia - Ruhil Hayati, Hamdan (Fakulti Agroteknologi dan Sains Makanan, 2010)
Oyster is a filter feeder that consumes a large volume of bacteria during ingestion activity. Totally, 28, 10 and 15 isolates of V. parahaemolyticus, V. vulnificus and V. alginolyticus were isolated from oyster, respectively. The morphological, physiological and biochemical studies were done with addition of commercial identification system BBL Crystal™ Kit. All isolates were motile Gram-negative; straight and curved rod; non-luminous, oxidase and catalase positive; sensitive to 0/129 (150(ig), glucose fermentative, indole formation, able to utilize starch, positive for both Oxidative and Fermentative, and p-hemolytic. All isolates did not produce H2S. All isolates also showed negative reactions for Voges Proskauer, ONPG and tetrazolium